An optimal defense strategy for phenolic glycoside production in Populus trichocarpa – isotope labeling demonstrates secondary metabolite production in growing leaves. Issue 2 (16th April 2014) - Massad, Tara Joy; Trumbore, Susan E.; Ganbat, Gantsetseg; Reichelt, Michael; Unsicker, Sybille; Boeckler, Andreas; Gleixner, Gerd; Gershenzon, Jonathan; Ruehlow, Steffen
Summary Large amounts of carbon are required for plant growth, but young, growing tissues often also have high concentrations of defensive secondary metabolites. Plants' capacity to allocate resources to growth and defense is addressed by the growth‐differentiation balance hypothesis and the optimal defense hypothesis, which make contrasting predictions. Isotope labeling can demonstrate whether defense compounds are synthesized from stored or newly fixed carbon, allowing a detailed examination of these hypotheses. Populus trichocarpa saplings were pulse‐labeled with 13CO2 at the beginning and end of a growing season, and the 13C signatures of phenolic glycosides (salicinoids), sugars, bulk tissue, and respired CO2 were traced over time. Half of the saplings were also subjected to mechanical damage. Populus trichocarpa followed an optimal defense strategy, investing 13C in salicinoids in expanding leaves directly after labeling. Salicinoids turned over quickly, and their production continued throughout the season. Salicin was induced by early‐season damage, further demonstrating optimal defense. Salicinoids appear to be of great value to P. trichocarpa, as they command new C both early and late in the growing season, but their fitness benefits require further study. Export of salicinoids between tissues and biochemical pathways enabling induction also needs research. Nonetheless, the investigation of defense production afforded by isotope labeling lends new insights into plants' ability to grow and defend simultaneously.